2020
DOI: 10.1186/s13071-019-3872-2
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae populations from Burkina Faso show minimal delayed mortality after exposure to insecticide-treated nets

Abstract: Background The efficacy of long-lasting insecticidal nets (LLINs) in preventing malaria in Africa is threatened by insecticide resistance. Bioassays assessing 24-hour mortality post-LLIN exposure have established that resistance to the concentration of pyrethroids used in LLINs is widespread. However, although mosquitoes may no longer be rapidly killed by LLIN exposure, a delayed mortality effect has been shown to reduce the transmission potential of mosquitoes exposed to nets. This has been postulated to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 33 publications
3
44
2
Order By: Relevance
“…In our setting, the longevity was expressed by the mortality both at 24 hours post exposure, and at the end of the gonotrophic cycle. These two mortalities were affected by exposure to LLIN at each gonotrophic cycle contrary to observation made in Burjina Faso where following single and multiple exposures to a PermaNet 2.0 LLIN only one of the four mosquito populations tested showed evidence of delayed mortality [38].in our study, it increases by twice between the first and fourth gonotrophic cycles in unexposed mosquitoes, while it tripled over the same interval in the exposed group. By the end of gonotrophic cycle 4, mosquitoes were aged 25 to 28 days.…”
Section: Discussioncontrasting
confidence: 99%
“…In our setting, the longevity was expressed by the mortality both at 24 hours post exposure, and at the end of the gonotrophic cycle. These two mortalities were affected by exposure to LLIN at each gonotrophic cycle contrary to observation made in Burjina Faso where following single and multiple exposures to a PermaNet 2.0 LLIN only one of the four mosquito populations tested showed evidence of delayed mortality [38].in our study, it increases by twice between the first and fourth gonotrophic cycles in unexposed mosquitoes, while it tripled over the same interval in the exposed group. By the end of gonotrophic cycle 4, mosquitoes were aged 25 to 28 days.…”
Section: Discussioncontrasting
confidence: 99%
“…With the exception of chlorfenapyr, which is known to be a slow-acting insecticide, we did not detect any delayed mortality effects for 72 hours following insecticidal exposure; the format and dose used for clothianidin testing (another slow-acting insecticide [45]) was instead intended to measure acute toxicity within a minute exposure period. Previous mathematical models using resistant mosquito colonies have suggested that sub-lethal insecticide treatment may still reduce vector lifespan and inhibit blood-feeding and host-seeking behaviours, thereby interrupting malaria transmission [46,47]. Our observations are more compatible with reports from Burkina Faso where different exposure regimens of wild, resistant An.…”
Section: Malaria Prevalencesupporting
confidence: 89%
“…populations to deltamethrin LLINs did not induce any delayed mortality [47]. To date there is a paucity of data regarding the interactions between insecticide resistance and Plasmodium development [48].…”
Section: Malaria Prevalencementioning
confidence: 95%
“…Births can only occur into generation i = 0 and vectors are assumed to survive up to a maximum of 10 gonotrophic cycles [42]. Using this model it is possible to calculate the parity of the population.…”
Section: Age Structurementioning
confidence: 99%